Influence of contact parameters on the coupling temperature of copper-brass electrical contacts. (June 2022) - Zuo, Xue; Du, Mengdi; Zhou, Yuankai
Highlights: The characteristics of transient temperature rise of electrical contact were analyzed. The distribution of coupling temperature field of sliding electrical contacts was studied. The optimal contact pressure increases with electric current, and decreases with sliding velocity. Abstract: The overheating phenomenon of slip ring will lead to wear failure of friction pair, and further affect the current-carrying efficiency. In order to study the temperature properties of slip ring, a friction and wear model with electric currents applied was established by COMSOL. The accuracy of the simulation was verified by the experiments. The distribution of coupling temperature field, and the influence of sliding speed, electric current density and contact pressure on the coupling temperature were studied. A phenomenon of "high temperature tailing" appears behind the contact area, and the trail length increases gradually with the time. The coupling temperature increases with electric current densities and sliding speeds. The MCT decreases rapidly at first and then increases gradually with the increase of contact pressure. There exists an optimal contact pressure to minimize the MCT. The optimal contact pressure increases with electric current densities, and decreases with sliding speed. The results may provide a theoretical basis for the temperature rise analysis and can improve the current-carrying efficiency of wind power slip ring.